Abundance and Distribution of Bivalves in Intertidal Zone of Batu Kalang Beach of Pesisir Selatan Regency West Sumatera Province - Ferdi Fajri; Afrizal Tanjung; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in December 2015 in the Batu Kalang Beach coastal area of the Pesisir Selatan Regency, West Sumatera Province, aimed to determine the distribution and abundance of bivalves in the intertidal zone. Bivalves samples were taken by using Quadrant Transect Sampling Method and sample was analyzed in Marine Biology Laboratory, Fisheries and Marine Sciences Facultyand data was investigated descriptively. Based on the result, upper zone has the lowest abundance that is 4,00 ind/m2. At middle zone the abundance of bivalves was about 4,11 ind/m2, this abundance higher than upper zone. Bivalves abundance on lower zone has the highest abundance that is 4,89 ind/m². Bivalves abundance that founded during research on Batu Kalang Beach was variated, which as the highest bivalves was Periglypta reticulate, founded 15 species and the lowest abundance of bivalves founded three species that Hemidonax sp, Gafrarium divaricatum, Codakia tigerina.Keywords: Bivalves, Distribution, Abundance, Batu Kalang Beach, West Sumatera